(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The purpose of research is highlighting the role of tax expenses in promoting direct foreign investment in Iraq, The main objective of the increase in the field of tax expenses is to manage the competition in the production of goods and services locally, in addition to the various qualities of the economical. As the search contributes to the idea of the role of the policy of the tax expenses in the promotion of foreign companies operating in Iraq. The analytical and transparent transparency used by adoption of cases of the relevant body of the tax body. For each image or form of tax expenses have been reliably related to the promotion of direct foreign investment, the taxpayers highlighted the annual controls, tax cuts as the sample was looking at the senior department of foreign companies for years of (2015 for 2017), the revision of ongoing operations was relied on the revenue for each financial year. There were cases of the taxi exemption for her. Under decision Council No. (167) of (2010), and companies were granted tax premises under the investment Law No. (13) Of (2006). The tools adopted in the data analysis process and financial statements were based on the instructions and annual controls out of the General Assembly of taxes through the ratios and tax profits, The research has submitted a number of important conclusions: The increase in tax expenses contributes to promoting direct foreign investment by initiating all appropriate conditions for foreign investment companies in the production of goods and services locally and to achieve competition for these goods from existence of existence. The research also provided a number of recommendations, most of the need to promote foreign investment by granting privileges and priorities for these companies, compared to national companies to develop the various economic and productive sectors.